Isolated with persistence or dynamically connected? Genetic patterns in a common granite outcrop endemic - Tapper, S.; Byrne, B.; Yates, C.; Keppel, Gunnar; Hopper, S.; Van Niel, K.; Schut, Tom; Mucina, Ladislav; Wardell-Johnson, Grant (Blackwell Science Ltd, 2014)
Aim - Granite outcrops are prominent throughout the world and harbour many endemic species. Their topographic complexity and range of environments have led to the hypothesis that they act as refugia facilitating the persistence of species through climate change. We evaluate this hypothesis by investigating the phylogeographic patterns in a common granite endemic shrub. Location - Granite outcrops of the Southwest Australian Floristic Region. Methods - Chloroplast haplotypes of 89 Kunzea pulchella individuals from 16 granite outcrops were determined from sequences of three chloroplast intergenic spacer regions. Phylogenetic reconstruction and divergence dating was inferred using Bayesian and Parsimony analyses and phylogenetic relationships between haplotypes were examined in relation to geographic distributions. Nuclear diversity and differentiation of populations were assessed through analysis of 11 nuclear microsatellite loci across 384 individuals from the 16 granite outcrops. Results - Kunzea pulchella exhibited low haplotype and allelic diversity within outcrops and high levels of divergence among outcrops, indicating an ancient restriction to specific outcrops with genetic drift as the main driver of evolution. Two divergent lineages were revealed in the chloroplast phylogeny datingto the Pliocene and potentially reflecting the initial impact of increased aridity prior to isolation on individual outcrops. Main conclusions - Rather than uncovering the typical pattern for Pleistocene refugia with contraction to, and expansion from particular granite outcrops, we observed persistence, prolonged isolation and divergence of populations. We suggest the persistence of K. pulchella on multiple outcrops through a period of considerable climatic change may be a result of broad climatic tolerances or contraction and expansion dynamics operating at microrefugial scales within outcrops. Our observations of low haplotype and allelic diversity within populations of K. pulchella provide some support for the latter. The enduring nature of K. pulchella and evolutionary potential of populations on individual out-crops accentuates the value of these environments for biodiversity conservation planning in a changing climate.